Developing a xenograft human tumor model in immunocompetent mice. (1st January 2018) - Basel, Matthew T.; Narayanan, Sanjeev; Ganta, Chanran; Shreshta, Tej B.; Marquez, Alejandro; Pyle, Marla; Hill, Jennifer; Bossmann, Stefan H.; Troyer, Deryl L.
Abstract: Animal models are essential to cancer research, but current xenograft models are limited in their utility especially due to the lack of an immune system. Here we demonstrate that a xenograft tumor model can be developed in immunocompetent mice by tolerizing murine fetuses to human tumor cells. A375 human melanoma cells were injected into day E14 fetuses and after birth mice were challenged with A375 cells to determine their ability to develop tumors. Intravenous injections of cells resulted in metastatic-like lung tumors, which were verified to be human in origin by immunohistochemistry and PCR. These results were replicated with several other human tumor types: BxPC3 (human pancreatic adenocarcinoma), MDA-MB-231 (human breast adenocarcinoma), M21 (human melanoma), and HeLa (human cervical adenocarcinoma). Development of an immunocompetent xenograft tumor model would allow the further elucidation of the interaction of the immune system with therapy in both preclinical research and patient derived xenografts. Highlights: Mice can be tolerized to human cells through pre-immune fetal injections. Tolerized mice do not reject human cells given after birth. When challenged with human tumor cells, tolerized mice develop neoplasms.